The Catholic Sovereign [Safety-Coach], a new Start from the Castle Windsor - a regular Out and Outer - (:unkn) unknown (Fores, S. W., 1829)
Scholarly notes may be added at a later date.
Needs must when Well-Drives
1 print : col.
Keywords: Caricatures; Cartoons; Carriages & coaches; Catholic emancipation; Great Britain -- Politics and government -- 1800-1837; Anti-Catholicism; Coaching (Transportation)